Use of Website as Information Media and Learning Media for Madrasah Students in Ngawi Regency (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to describe the quality of information submitted on the website at one of the Madrasahs in Ngawi Regency about the use of technology as a medium for disseminating information. The method used in this study is to use qualitative descriptive research. The data was obtained from content analysis and interviews as well as in-depth observations conducted in one of the Madarasahs in Ngawi Regency. The results showed that the use of information technology that is actively used is Instagram and YouTube, information dissemination and promotion that is actively managed and used by Madrasah.